The Role of Digital Memes in Digital Media Platforms in Shaping Saudi Cultural Identity Among University Students - Abo Bakr, Rehab Tharwat ABD EL Ghani; Al-Shahrani, Layla Falah Sahman; Al-Dossary, Rawaiyah Tariq Rashed; Alnaimi, Fatimah Adel Rashed; Al-Amrai, Reem Sulaiman Ali; Al-Mutairi, Shatha Muteb Nasser (Journal of Posthumanism, 2026)
The aim of this study was to explore the role of digital memes on digital media platforms in shaping Saudi cultural identity among students at Imam Abdulrahman Bin Faisal University. The study examined the relationship between meme usage and cultural identity, with a focus on how memes influence both local cultural pride and global cultural exposure. Using a descriptive survey method, a structured questionnaire was developed and administered to a stratified random sample of 650 students from the university. The findings indicated that digital memes play a significant role in shaping cultural identity, with 65% of students frequently engaging with memes to express social situations and showcase cultural symbols. However, the study also found that 40% of students feel that global memes sometimes weaken adherence to local traditions. Based on these results, the study recommends raising awareness about the role of digital memes in cultural identity formation, encouraging the creation of memes that reflect Saudi culture, and promoting critical engagement with memes to preserve cultural authenticity while navigating global influences.